Moringa oleifera Seed Extract Alleviates Scopolamine-Induced Learning and Memory Impairment in Mice - Zhou, Juan; Yang, Wu-shuang; Suo, Da-qin; Li, Ying; Peng, Lu; Xu, Lan-xi; Zeng, Kai-yue; Ren, Tong; Wang, Ying; Zhou, Yu; Zhao, Yun; Yang, Li-chao; et al. (Frontiers in Pharmacology, 2018)
The extract of M. oleifera seeds has been shown to possess various pharmacological properties. In the present study, we evaluated the neuropharmacological effects of 70% ethanolic M. oleifera seed extract (MSE) on memory impairment caused by scopolamine injection in mice using the passive avoidance and Morris water maze (MWM) tests. MSE (250 or 500 mg/kg) was administered to mice by oral gavage for 7 or 14 days, and memory impairment was induced by intraperitoneal injection of scopolamine (2 mg/kg) for 1 or 6 days. Mice that received scopolamine alone showed impaired learning and memory retention and considerably decreased cholinergic system reactivity and neurogenesis in the hippocampus. MSE pretreatment significantly attenuated scopolamine-induced memory impairment and enhanced cholinergic system reactivity and neurogenesis in the hippocampus. In addition, the expression levels of phosphorylated Akt, ERK and CREB in the hippocampus were significantly decreased by scopolamine, but these decreases were reversed by MSE treatment. These results suggest that MSE-induced ameliorative cognitive effects are mediated by enhancement of the cholinergic neurotransmission system and neurogenesis via activation of the Akt, ERK and CREB signaling pathways. These findings suggest that MSE could be a potent neuropharmacological drug against amnesia, and its mechanism might be modulation of cholinergic activity via the Akt, ERK and CREB signaling pathways.